Experimental Characterisation of Swirl Stabilized Annular Stratified Flames - Bonaldo, Alessio (Cranfield University, 2007)
A burner for investigating lean stratified premixed flames propagating in intense isotropic turbulence has been developed. Lean pre-mixtures of methane at different equivalence ratios are divided between two concentric co-flows to obtain annular stratification. Turbulence generators are used to control the level of turbulence intensity in the oncoming flow. A third annular weakly swirling air flow provides the flame stabilization mechanism. A fundamental characteristic is that flame stabilization does not rely on flow recirculation. The flames are maintained at a position where the local mass flux balances the burning rate, the result is a freely propagating turbulent flame front. The absence of physical surfaces in the vicinity of the flame provides free access for laser diagnostics. Stereoscopic Planar Image Velocimetry (SPIV) has been applied to obtain the three components of the instantaneous velocity vectors on a vertical plane above the burner outlet where the flames propagate. The instantaneous temperature fields have been determined through Laser Induced Rayleigh (LIRay) scattering. Planar Laser Induced Fluorescence (PLIF) on acetone has been used to calculate the average equivalence ratio distributions. Instantaneous turbulent burning velocities have been extracted from SPIV results, while flame curvature and flame thermal thickness values have been calculated using the instantaneous temperature fields. The probability distributions of these quantities have been compared considering the separate influence of equivalence ratio stratification and turbulence. It has been observed that increased levels of turbulence determine higher turbulent burning velocities and flame front wrinkling. Flames characterized by stronger fuel stratification showed higher values in turbulent burning velocities. From the curvature analysis emerged that increased fuel concentration gradients favour flame wrinkling, especially when associated with positive small radius of curvature. This determines an increased surface area available for reaction that promotes a faster propagation of the flame front in the oncoming combustible mixtures.